BODY DISCIPLINE IN THE MOVIE “TURNING RED”: FOUCALDIAN DISCOURSE - Neisya, Neisya; Aprilia, Fitria; Triwulandari, Elga (Lire Journal (Journal of Linguistics and Literature), 2024)
This research explores the concept of body discipline and its implications in the movie "Turning Red," focusing on the character Meilin Lee and her portrayal of female regulation. The research method used in this study is qualitative research. Specifically, the study uses descriptive research, primarily focusing on describing the main character's characteristics. For data collection, the researchers watched the movie Turning Red repeatedly and highlighted the issue related to the research problem through dialogues and scenes. Meanwhile, in analyzing the data, the researchers classified and analyzed the types of body discipline and impact on Meilin Lee through the lens of Foucault's theory. The analysis reveals that family and social space significantly influence the constraints imposed on the main character, depicted as the Red Panda, transforming her behavior, resulting in anger or frustration, shock, and eventually acceptance. Through this research, the movie "Turning Red" serves as a platform to explore and highlight the effects of body discipline on individuals, particularly in the context of female regulation.